NEW TRENDS IN THE TREATMENT OF ADVANCED OVARIAN CANCER - S. V. Khohlova (Опухоли женской репродуктивной системы)
Author reviews recent clinical studies of advanced ovarian cancer treatment with new chemotherapeutic agents. New schemes and modifications of available standard regimens are described, regimens with sequential administration of agents are evaluated and data concerning the use of new cytostatic agents and three-component combinations are reviewed.